2007
DOI: 10.1097/wnr.0b013e32821c51fe
|View full text |Cite
|
Sign up to set email alerts
|

Myricetin reduces 6-hydroxydopamine-induced dopamine neuron degeneration in rats

Abstract: The effects of myricetin on 6-hydroxydopamine (6-OHDA)-induced neurodegeneration in the substantia nigra-striatum system were investigated. By high-performance liquid chromatography electrochemical detection, we showed that the dopamine content in the striatum decreased after 6-OHDA treatment, which could be restored by myricetin. The immunohistochemistry and semiquantitative reverse transcription-PCR studies showed that myricetin could prevent the 6-OHDA-induced decrease of tyrosine hydroxylase positive neuro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
29
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
2
1

Relationship

3
7

Authors

Journals

citations
Cited by 48 publications
(31 citation statements)
references
References 15 publications
1
29
0
1
Order By: Relevance
“…6-OHDAtreated animals exhibit the major hallmarks of PD, including loss of dopaminergic neurons in the SN. In the present study, we observed increased iron levels in the SN of PD models where dopaminergic neuronal degeneration was found, in accordance with our previous studies as well as with those of others [7,21,22]. Ferrous iron is harmful to cells because of its ability to react with hydrogen peroxide to form highly reactive hydroxyl radicals.…”
Section: Discussionsupporting
confidence: 80%
“…6-OHDAtreated animals exhibit the major hallmarks of PD, including loss of dopaminergic neurons in the SN. In the present study, we observed increased iron levels in the SN of PD models where dopaminergic neuronal degeneration was found, in accordance with our previous studies as well as with those of others [7,21,22]. Ferrous iron is harmful to cells because of its ability to react with hydrogen peroxide to form highly reactive hydroxyl radicals.…”
Section: Discussionsupporting
confidence: 80%
“…Myricetin (2, 5, 7, 3′, 4′, 5′-pentahydroxylflavonol) is a widely distributed flavonoid [14], which has been reported to have a variety of biological effects, such as anticancer, antioxidant, antidiabetic, prevention of apoptosis, and neuron degeneration [1417]. Myricetin is also an important bioactive compound present in some medicinal herbs, for example, St. John's Wort [18], which have hypnotic and antidepressant effects.…”
Section: Introductionmentioning
confidence: 99%
“…A high level of iron has been found in the SN of parkinsonian [28] and PD mouse models [17,19,[29][30][31][32][33][34][35] , where α-synuclein aggregation also exists.…”
Section: Discussionmentioning
confidence: 99%